2009
DOI: 10.1124/jpet.109.154781
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein and Breast Cancer Resistance Protein Influence Brain Distribution of Dasatinib

Abstract: The novel tyrosine kinase inhibitor dasatinib (Sprycel; BMS-354825) is approved for use in imatinib (Gleevec; STI 571)-resistant or -intolerant chronic myelogenous leukemia and may be useful for other tumors in the central nervous system (CNS). The objective of this study was to investigate the role of Pglycoprotein (P-gp) and breast cancer resistance protein (BCRP) in modulating the CNS penetration of dasatinib. Results from the in vitro studies indicate that cellular delivery of dasatinib is significantly li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
184
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(197 citation statements)
references
References 29 publications
13
184
0
Order By: Relevance
“…The expression of both Bcrp and Pgp on brain microvessel endothelial cells has been demonstrated, and it has been shown that Bcrp and Pgp work in concert in regulating the penetration of drugs across the BBB (Chen et al, 2009;Polli et al, 2009;Kodaira et al, 2010). For the cosubstrates of both Bcrp and Pgp, however, the function of Bcrp in restricting drug brain penetration is often masked because dmd.aspetjournals.org of the more pronounced role played by Pgp at the BBB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of both Bcrp and Pgp on brain microvessel endothelial cells has been demonstrated, and it has been shown that Bcrp and Pgp work in concert in regulating the penetration of drugs across the BBB (Chen et al, 2009;Polli et al, 2009;Kodaira et al, 2010). For the cosubstrates of both Bcrp and Pgp, however, the function of Bcrp in restricting drug brain penetration is often masked because dmd.aspetjournals.org of the more pronounced role played by Pgp at the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…For the cosubstrates of both Bcrp and Pgp, however, the function of Bcrp in restricting drug brain penetration is often masked because dmd.aspetjournals.org of the more pronounced role played by Pgp at the BBB. The function of Bcrp can be observed only when the activities of both Bcrp and Pgp are disrupted either by the Pgp/Bcrp dual inhibitor GF120918 or in Mdr1a/1b(Ϫ/Ϫ)/Bcrp(Ϫ/Ϫ) mice (Breedveld et al, 2005;Bihorel et al, 2007;de Vries et al, 2007;Giri et al, 2008;Chen et al, 2009). Therefore, the identification and characterization of a Bcrp-selective substrate becomes necessary when investigating Bcrp function in regulating drug transport across the BBB, as well as evaluating Bcrp-mediated drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), and they are most are primarily cleared via metabolism by CYP3A4. These chemical features are also typical for substrates of ATP-binding cassette (ABC) transporters (Polli et al, 2008;Chen et al, 2009;Oostendorp et al, 2009;Shukla et al, 2009;Carcaboso et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These results showed no effect of abcg2 2/2 , a marked increase in brain exposure in abcb1a/b 2/2 , and an even greater increase in the triple knockout. The ability of P-gp and bcrp to work together to limit brain disposition has also been described for lapatinib and dasatinib (Chen et al, 2009;Polli et al, 2009). The results of Poller et al (2011) suggested that the mouse mdr1 limits the brain distribution of axitinib, with the role of bcrp being unclear.…”
Section: Transporters For Axitinibmentioning
confidence: 99%